The effect of billet wall thickness on the rotary compression process for hollow parts - Tomczak, Janusz (Strojniški vestnik, 2015)
This paper presents the numerical and experimental results of investigating the effect of geometrical parameters of tubular specimens on the rotary compression process for hollow axisymmetric shafts with central necking, and their accuracy. The numerical investigation was performed using the finite element method (FEM) with the Simufact Forming simulation software suite. The simulations investigated the effect of tubular specimen wall thickness on the kinematics of metal flow and the geometry of produced shafts. The results were validated in experimental tests using a forging machine designed specifically for this purpose.
Keywords: eksperimenti; finite element method; metoda končnih elementov; preoblikovanje kovine; rotacijsko stiskanje; votle gredi; votli deli